Accounting for Electronic Polarization Effects in Aqueous Sodium Chloride via Molecular Dynamics Aided by Neutron Scattering - Kohagen, Miriam; Mason, Philip E; Jungwirth, Pavel (The journal of physical chemistry. B, 2016)
Modeled ions, described by nonpolarizable force fields, can suffer from unphysical ion pairing and clustering in aqueous solutions well below their solubility limit. The electronic continuum correction takes electronic polarization effects of the solvent into account in an effective way by scaling the charges on the ions, resulting in a much better description of the ionic behavior. Here, we present parameters for the sodium ion consistent with this effective polarizability approach and in agreement with experimental data from neutron scattering, which could be used for simulations of complex aqueous systems where polarization effects are important.